2021
DOI: 10.1111/icad.12475
|View full text |Cite
|
Sign up to set email alerts
|

The role of a rosette‐shaped plant (Eryngium horridum, Apiaceae) on grassland spiders along a grazing intensity gradient

Abstract: Rosette‐shaped plants can amplify the diversity of predator arthropods and act as potential shelters for these animals in grassland ecosystems under grazing effect. Here we evaluated the contribution of a vertical rosette‐shaped plant (Eryngium horridum) to patterns of spider diversity and functional traits in subtropical grasslands under different grazing intensities. We used a common sub‐shrub (Baccharis crispa) and the herbaceous vegetation as reference microhabitats. Sampling was conducted in 23 plots desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Such trend can be observed in the diversity of plant communities (Ross et al, 2016;Pakeman et al, 2019), flies (Clement et al, 2018), butterflies (Fraser et al, 2014), rodents (Evans et al, 2015;Li et al, 2019b), and birds (Fraser et al, 2014;Evans et al, 2015). This effect may have been observed only on Ambush hunters and Other hunters because, even though these guilds are known to hunt on the surface of flowers and leaves, with a higher dominance of families like Thomisidae and Salticidae than other families, they are also capable of adopting hunting strategies on the ground and other substrates, thus not relying only in one type of vegetation structure (Gomes et al, 2018;Joseph et al, 2018;Lyons et al, 2018b,c;da Silva Bomfim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such trend can be observed in the diversity of plant communities (Ross et al, 2016;Pakeman et al, 2019), flies (Clement et al, 2018), butterflies (Fraser et al, 2014), rodents (Evans et al, 2015;Li et al, 2019b), and birds (Fraser et al, 2014;Evans et al, 2015). This effect may have been observed only on Ambush hunters and Other hunters because, even though these guilds are known to hunt on the surface of flowers and leaves, with a higher dominance of families like Thomisidae and Salticidae than other families, they are also capable of adopting hunting strategies on the ground and other substrates, thus not relying only in one type of vegetation structure (Gomes et al, 2018;Joseph et al, 2018;Lyons et al, 2018b,c;da Silva Bomfim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Two neotropical spider species, the theridiid Latrodectus geometricus and the araneid Alpaida quadrilorata , are both found in association with Paepalanthus bromelioides [ 73 ]. This rosette-structured plant provides the spiders with the structural necessities for web construction and may also offer refuge and protection from predators [ 23 , 75 ]. More importantly, P. bromelioides is considered to be a protocarnivorous plant that obtains nutrients from insects with the aid of digestive mutualists, namely L. geometricus and A. quadrilorata [ 73 ].…”
Section: Spider–plant Associationsmentioning
confidence: 99%
“…lineatus preferred to inhabit tall, thorny, and even poisonous plants. Thorny plants offer protection against predators (e.g., birds) and reduce the risk of disturbances from large herbivorous animals (e.g., cattle and other browsing/grazing mammals) that can damage or destroy spider webs [ 54 , 72 , 75 , 80 ]. Ruch et al [ 72 ] demonstrated that S .…”
Section: Spider–plant Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The removal of above-ground plant biomass provoked by chronic grazing (Tälle et al 2016; Pett and Bailey 2019; Ferreira et al 2020; da Silva Bomfim et al 2021) directly affects the primary hunting strategy of orb-weavers, the ability to build webs using the tridimensional vegetal structure (Nogueira and Pinto-da-Rocha 2016). Without physical structures to build their web, species are unable to find prey (Torma et al 2019; Helden et al 2020; Fischer et al 2021) and mates (Cory and Schneider 2018; Weiss and Schneider 2021), as well as avoid predation (Blackledge and Wenzel 1999; da Silva Bomfim et al 2021; Narimanov et al 2021). Consequently, the simplification of habitat structure induced by grazing can culminate in the decline of local populations, resulting in the exclusion of orb-weaver species from grasslands (Oyarzabal and Guimarães 2021).…”
Section: Introductionmentioning
confidence: 99%